2022
DOI: 10.21274/sosebi.v2i2.6428
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Modal Usaha, Jam Kerja Dan Lama Usaha Terhadap Pendapatan Usaha Mikro Kecil Menengah Pedagang Pasar Gambar Kecamatan Wonodadi Kabupaten Blitar

Abstract: Abstrak: Penelitian ini bertujuan mengetahui pengaruh modal usaha, jam kerja, dan lama usaha terhadap pedagang usaha, mikro, kecil, dan menengah (UMKM) di pasar Gambar Wonodadi Blitar baik secara bersamaan maupun sebagian. Teknik penelitian asosiatif dan kuantitatif yang digunakan dalam penelitian ini. Rumus slovin dipakai dengan teknik sampel penelitian, dan total 80 tanggapan responden dianalisis. Uji multikolinearitas, analisis regresi berganda, dan uji asumsi klasik digunakan untuk menganalisis data dalam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
1
3
0
2
Order By: Relevance
“…Utami (2022) and Hamsiah et al (2023) found that business capital has a positive and significant effect on merchant income. On contrary, Alkumairoh & Warsitasari (2022) and Ferdiani & Widiastuti (2023) shiwed that business capital does not positively impact the income of small and medium enterprises merchants. The amount of capital does not necessarily have an impact on increasing income because with a large number of goods in stock which is not accompanied by a large amount of consumer interest, there can be a decrease in the quality of the goods in stock which can change the selling price, in addition to the possibility of damage to goods, resulting in losses for sellers and affecting income (Alkumairoh & Warsitasari, 2022).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Utami (2022) and Hamsiah et al (2023) found that business capital has a positive and significant effect on merchant income. On contrary, Alkumairoh & Warsitasari (2022) and Ferdiani & Widiastuti (2023) shiwed that business capital does not positively impact the income of small and medium enterprises merchants. The amount of capital does not necessarily have an impact on increasing income because with a large number of goods in stock which is not accompanied by a large amount of consumer interest, there can be a decrease in the quality of the goods in stock which can change the selling price, in addition to the possibility of damage to goods, resulting in losses for sellers and affecting income (Alkumairoh & Warsitasari, 2022).…”
Section: Introductionmentioning
confidence: 94%
“…On contrary, Alkumairoh & Warsitasari (2022) and Ferdiani & Widiastuti (2023) shiwed that business capital does not positively impact the income of small and medium enterprises merchants. The amount of capital does not necessarily have an impact on increasing income because with a large number of goods in stock which is not accompanied by a large amount of consumer interest, there can be a decrease in the quality of the goods in stock which can change the selling price, in addition to the possibility of damage to goods, resulting in losses for sellers and affecting income (Alkumairoh & Warsitasari, 2022). discovered that the cost of renting business premises influences the income of merchants in a fish market, while Munawwarah (2022) found that rent costs do not affect the income of merchants in another market.…”
Section: Introductionmentioning
confidence: 94%
“…Determination of the Number of samples using an error tolerance limit of 10% in the following way. Based on the calculation of the Slovin formula, the sampling technique uses the same random sampling technique using the Slovin equation to determine the sample formulation using an error rate of 10% or 0.1 [11]. The reason for using a 10% error (90% confidence level) is that it refers to the maximum error rate that can be tolerated in social science research, so it is known that the total sample in this study is as many as 94 respondents.…”
Section: Determination Of Population and Samplementioning
confidence: 99%
“…Dalam menjalankan bisnis, pelaku usaha harus memastikan bahwa jumlah modal kerja yang tersedia lebih besar dari penggunaannya dalam operasional agar menghindari kerugian dalam usaha. Tetapi penelitian yang dilakukan oleh (Sidik & Ilmiah, 2022) dan (Alkumairoh & Warsitasari, 2022) menunjukkan modal kerja yang besar tidak selalu meningkatkan pendapatan pelaku usaha, seperti persediaan barang menyebabkan biaya penyimpanan lebih tinggi dan penurunan nilai aset dari persediaan yang tidak terjual.…”
Section: Tabel 1 Jumlah Pengunjung Destinasi Wisata Danau Cipondohunclassified
“…Apabila jumlah persediaan barang yang diproduksi terlalu banyak dibandingkan dengan kebutuhan pengusaha, maka akan terjadi kerugian karena adanya kerusakan barang, penurunan kualitas, biaya perawatan yang meningkat, dan berdampak pada penurunan pendapatan. Kemudian penelitian yang dilakukan oleh (Alkumairoh & Warsitasari, 2022) sesuai dengan penelitian ini yang menunjukkan bahwa tingginya modal tidak selalu berdampak pada peningkatan pendapatan karena jika terdapat banyak persediaan barang namun sedikit minat dari konsumen, maka kualitas barang persediaan bisa menurun dan mengubah harga jual. Selain itu, kemungkinan kerusakan barang juga dapat terjadi yang akan mengakibatkan kerugian bagi penjual dan berdampak pada pendapatan.…”
Section: Pengaruh Modal Kerja Terhadap Pendapatan Pelaku Wirausahaunclassified